Catalytic dehydration of 2 propanol over Al₂O₃–Ga₂O₃ and Pd/Al₂O₃–Ga₂O₃ catalysts - Díaz de Leon, J. N.; Cruz-Taboada, A.; Esqueda-Barron, Y.; Alonso-Nuñez, G.; Loera-Serna, S.; Venezia, A. M.; Poisot Vazquez, Martha Emilia; Fuentes-Moyado, S. (Catalysis Today, 2020)
A series of mixed Al₂O₃–Ga₂O₃ oxides were prepared with different Ga₂O₃ content (labeled as AlGa-x; where x is the wt% of Ga₂O₃) by precipitation method. The oxides were then used as supports of palladium (2 wt%) catalysts (labeled as Pd/AlGa-x). Both series of samples, AlGa-x and Pd/AlGa-x, were characterized by several techniques such as Raman spectroscopy, XPS, XRD, SEM, and HRTEM, and were tested in the 2-propanol dehydration reaction. The steady-state conversions displayed by the Pd/AlGa-x series were almost twice those obtained for the AlGa-x series in all the range of tested temperatures. It was worth noting that the presence of palladium changed the yield observed for the AlGa-x series mainly at low temperatures. While at high temperatures, the Lewis acidity provided by the well-dispersed Pd nanoparticles increased the activity considerably and improved the propylene production. A balance between the dispersion of palladium and the surface acidity, both related to the Ga₂O₃ content, was responsible for the observed catalytic behavior.
Keywords: Deshidratación catalítica; Paladio; Óxidos mixtos